Information system for generation of engineering mechanics practical works assignments and their inspection - Šešok, Dmitrij; Syrus, Leonidas (Lietuvos matematikos rinkinys, 2021)
The technology for automatization of lecturer’sworkplace is presented in the paper, enhancing and simplifying the preparation of assignments for practical works and their inspection. The main focus of paper is placed on the inspection of students’works.  The informational system created and exploited at the department of EngineeringMechanics, Vilnius Gediminas TechnicalUniversity, is described. Similar principles may be employed also for analogical systems of generating of assigments for practical works as well as inspection of them for other subjects (mathematics, informatics, etc).
Keywords: information system; databases; creation of assignments